침술에 의한 안구천공과 시야장애 1예 - 강현승, 이동규, 임수진, 김형은, 권오웅Hyunseung Kang MD Dong Kyu Lee MD Su Jin Lim MD Hyoung Eun Kim MD Oh Woong Kwon MD PhD (Daihan angwa haghoi jabji, 2013)
목적: 침술에 의한 안구천공 및 선형 망막찢김에서 다초점국소망막전위도상 정상 망막기능을 보이나 시야장애가 지속된 증례를 경험하였기에 이를 보고하고자 한다. 증례요약: 42세 여자가 안와 주변부에 침을 맞은 후 우안 시력저하가 발생하였고, 소량의 유리체 출혈 및 후극부 망막찢김 진단 하에장벽 레이저 광응고술을 시행받았다. 3개월 후, 시력저하 및 변형시 악화되었고 안저검사상 선형의 망막찢김과 레이저 반흔, 황반부에망막끌림을 동반한 망막전막이 관찰되었다. 빛간섭단층촬영에서 망막신경섬유조직을 포함한 전층 망막찢김이 관찰되었다. 다초점국소망막전위도는 정상 소견을 보였으나 자동시야검사상 이측 시야결손이 관찰되었다. 망막전막 제거술을 시행하여 교정시력이 1.0으로회복되었고 변형시도 일부 호전되었으나, 시야결손은 지속되었다. 결론: 주사침에 의한 안구천공은 주로 외상에 의해 발생하며 흔하지 않은 합병증으로, 그에 대한 다양한 안과 검사를 보고한 경우는드물다. 국내에서는 아직 보고된 바 없는 침술에 의한 안구천공 및 망막찢김에서 정상 망막기능을 보임과 동시에 망막신경섬유의 절단에 의한 시야장애가 지속된 증례를 경험하였기에 이를 보고하는 바이다. Purpose: To report a case of globe perforation and linear retinal tear after periocular acupuncture therapy which resulted in persistent temporal field defect with normal retinal function evidenced by multifocal electroretinogram (MERG). Case summary: A 42-year-old female presented with decreased visual acuity and pain in her right eye after a periocular acupuncture therapy for blepharospasm. At initial presentation, the best corrected visual acuity (BCVA) was 0.08 in the injured eye and the intraocular pressure was 15 mmHg. Ultrasonography showed minimal vitreous hemorrhage and fundus examination revealed a linear retinal tear in the posterior pole sparing the macula. Consequently, barrier laser photocoagulation was performed around the lesion. The patient suffered from metamorphopsia and persistent decreased visual acuity even after 3 months. On fundus examination, epiretinal membrane with macular pucker was observed on the macula. Spectral domain optical coherence tomography (SD-OCT) revealed retinal nerve fiber layer defect with a full-thickness posterior wall tear. Multifocal electroretinogram showed normal retinal function; however, Humphrey visual field test demonstrated field defect corresponding to the injury. A 25-gauge pars plana vitrectomy was performed with membranectomy and ILM peeling. One month postoperatively, improvement in BCVA and metamorphopsia was achieved;however, the scotomata remained unchanged. Conclusions: Ocular perforation or retinal tear caused by an acupuncture needle is a rare condition that has not been reported previously in Korea. Furthermore, no case of traumatic visual field defect with preserved retinal function has been reported elsewhere. Hence, the authors present a case of isolated visual field defect without retinal dysfunction following full-thickness retinal tear caused by an acupuncture needle. KCI Citation Count: 2